A Study Of Hyperemesis Gravidarum In IT Professional Women: A Cross-Sectional Study - Deshpande, Hemant; Pojala, Ramyapriya (Journal of Neonatal Surgery, 2025)
Introduction: Women with hyperemesis gravidarum experience severe nausea and vomiting symptoms which cause significant health problems for both the mother and fetus. The combination of extensive working hours and intensified workplace pressure makes women in the information technology (IT) field a unique population. Objective: This study aims to study the prevalence of HG amongst IT professional women and to study the socio-demographic and occupational determinants related to it as well as to study the maternal and foetal outcomes in this cohort. Methods: It was a questionnaire-based survey that was sent to 128 pregnant or recently delivered women working in the IT sector, and this was a cross-sectional study. Data was collected in the form of HG symptoms, occupational stress levels and numerous socio-demographic characteristics. A snowball sampling strategy was used for recruiting participants across multiple IT companies. Results: The participants' prevalence of HG was 15.63%, which is far higher than the average for the world. Correlations were not statistically significant, but younger age, first pregnancy and high work stress were found to be contributory variables. Maternal outcomes exposed HG-related problems, however, those with a HG diagnosis were not hospitalised at a significantly different rate than those without. Efficient treatment did not substantially differ birth weight preterm birth rates and other foetal outcomes. Conclusion: The study also notes that women working in IT have a higher prevalence of HG, which is likely exacerbated by work-related stress. While maternal and fetal outcomes were generally positive, the results indicate that use of alternative-focused interventions to address both medical and workplace challenges is needed. Employers and healthcare providers should together help pregnant women do a stressful job and also ensure that the pregnant woman gets all the appropriate care and that their stress (and the effects of HG) does not impact her health.